Measuring volatile emissions from moss gametophytes: A review of methodologies and new applications. (14th April 2022) - Brennan, Danlyn L.; Kollar, Leslie M.; Kiel, Scott; Deakova, Timea; Laguerre, Aurélie; McDaniel, Stuart F.; Eppley, Sarah M.; Gall, Elliott T.; Rosenstiel, Todd N.
Abstract: Mosses inhabit nearly all terrestrial ecosystems and engage in important interactions with nitrogen‐fixing microbes, sperm‐dispersing arthropods, and other plants. It is hypothesized that these interactions could be mediated by biogenic volatile organic compounds (BVOCs). Moss BVOCs may play fundamental roles in influencing local ecologies, such as biosphere–atmosphere–hydrosphere communications, physiological and evolutionary dynamics, plant–microbe interactions, and gametophyte stress physiology. Further progress in quantifying the composition, magnitude, and variability of moss BVOC emissions, and their response to environmental drivers and metabolic requirements, is limited by methodological and analytical challenges. We review several sampling techniques with various analytical approaches and describe best practices in generating moss gametophyte BVOC measures. We emphasize the importance of characterizing the composition and magnitude of moss BVOC emissions across a variety of species to better inform and stimulate important cross‐disciplinary studies. We conclude by highlighting how current methods could be employed, as well as best practices for choosing methodologies.